THE MODEL OF STRENGTHENING NATIONAL IDENTITY IN THE CADRE PROCESS OF STUDENT ORGANIZATION - Sjam, Darda Abdullah; Budimansyah, Dasim; Nurdin, Encep S.; Malihah, Elly (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2021)
This study aims to identify the model of strengthening the national identity through the cadre pattern in the Islamic Student Association organization (HMI). This study applied a qualitative approach with a case study method. Student organizations have a crucial role in providing insight, sense, and spirit of Indonesian nationalism that is wrapped in the frame of Unity in Diversity. One of the challenges faced by a student organization in Indonesia is the ability of this organization to protect its noble goals from certain interests, which can direct the activities to the issues that violate the motto. In this context, cadre in student organizations must strive to foster and strengthen the spirit of nationalism. The presence of a student religious organization provides its uniqueness that is noteworthy to study. Therefore, this study will identify how the concept of student religious organization regeneration, especially the Islamic Student Association. In this article, the researcher views that the cadre of a religious student organization such as the Islamic Student Association has a very unique and strong style of regeneration. It can be observed from the numerous cadres of Islamic Student Association who work in government, non-governmental organizations, and other sectors who are highly open with differences and voice about the importance of togetherness in unity, which is based on the ideology of struggle, i.e., pluralism, democracy, state administration, and law enforcement. The three struggle programs are determinative factors for caring for the National Identity (Unity in Diversity).